1990
DOI: 10.1136/jnnp.53.10.824
|View full text |Cite
|
Sign up to set email alerts
|

The frequency, causes and timing of death within 30 days of a first stroke: the Oxfordshire Community Stroke Project.

Abstract: In a prospective, community-based study of 675 consecutive patients with a first-ever stroke, of whom over 90% had computed tomography (CT) The age-adjusted relative risk of death for patients who had been functionally dependent pre-stroke was not significantly greater (1-8, 95% confidence interval 0 to 4 3). There was a significant trend for CFR to increase with age (Chi square for trend = 4 0, p < 0 05). This relationship was found in those patients who had been functionally independent prestroke (Chi squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
3
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(170 citation statements)
references
References 28 publications
10
151
3
6
Order By: Relevance
“…In Brazil, the results seem to vary slightly, depending on other factors such as the sample size and the region where the study was conducted, varying from 5 to 24.6% 4,11,12 . These data confirm a global trend of a significant reduction in the death rates related to disease 13 . In Oxfordshire, United Kingdom, during the periods between 1981 and 1984 and between 2002 and 2004, the death rates decreased by 20 to 40%.…”
Section: Discussionsupporting
confidence: 76%
“…In Brazil, the results seem to vary slightly, depending on other factors such as the sample size and the region where the study was conducted, varying from 5 to 24.6% 4,11,12 . These data confirm a global trend of a significant reduction in the death rates related to disease 13 . In Oxfordshire, United Kingdom, during the periods between 1981 and 1984 and between 2002 and 2004, the death rates decreased by 20 to 40%.…”
Section: Discussionsupporting
confidence: 76%
“…Patients with ICH have a higher early case fatality than do those with ISs. In CT-based studies, patients with ICH showed shortterm case fatality rates between 35% and 55% (Broderick et al, 1989;Bamford et al, 1990;Rosenow et al, 1997). However, at 2-year follow-up, the case fatality increased by only 3.4% to 38% in one study (Rosenow et al, 1997).…”
Section: The Influence Of Differences Between Patient Groupsmentioning
confidence: 99%
“…The frequency of infection in patients with acute stroke has been the subject of numerous clinical studies. Owing to different designs, patient selection criteria, diagnostic criteria, timing of assessment, and duration of follow-up, the results vary considerably, with a reported incidence of infection up to 90 % [9][10][11][12][13]. Almost all studies described pneumonia as the most frequent type of infection after stroke, followed by urinary tract infection [6].…”
Section: Rationale Behind Prophylactic Antibiotic Therapy In Strokementioning
confidence: 99%